Analisis Kinerja Keuangan Menggunakan Dupont System - Rosdiana, Baiq Mia; Husnaini, Wahidatul (Fakultas Ekonomi dan Bisnis Unram, 2025)
The Du Pont system is a comprehensive analysis that covers all activities and profit margins on sales to show the ratios that influence each other in determining the profitability of assets in which there are several financial ratios used in this study including Net Profit Margin, Total Asset Turn Over, Return On Investment, Equity multiplier, and Return on equity. This study was conducted to determine how effective the company is in managing the company's financial performance. This study aims to determine the financial performance of the company PT. Indosat Tbk and PT. Telkom (Persero) Tbk in 2020-2024 which is measured using the Du Pont system method. The approach used is comparative descriptive with secondary data obtained from the company's annual financial reports. The population in this study is PT. Indosat Tbk and PT Telkom (Persero) Tbk. The results of this study indicate that the company's financial performance measured using the Du Pont system, PT Indosat Tbk is better than PT Telkom (Persero) Tbk which can be seen from the value of return on investment and return on equity value.